2017
DOI: 10.1111/1440-1681.12692
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren protects against myocardial ischaemia‐reperfusion injury via an endothelial nitric oxide synthase dependent manner

Abstract: Aliskiren, a direct renin inhibitor, has shown potent ability to attenuate hypertension. Our previous research has found that aliskiren protected against myocardial ischaemia-reperfusion (I/R) injury and enhanced phosphorylation of endothelial nitric oxide synthase (eNOS) in spontaneously hypertensive rats. However, whether the cardioprotective effect of aliskiren against myocardial I/R injury was eNOS-dependent is unknown. In the present study, 12-week-old male eNOS knockout (eNOS ) and wild-type C57BL/6J mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The Alisk in the dose of 50 mg/kg improved bone alveolar loss and decreased inflammatory process. Corroborating with the literature, the dose used in the present study was also observed to decrease blood pressure, and renin–angiotensin II level in mice and attenuated steatosis and inflammation in mice (Lee et al, 2013; Wang et al, 2015; Chen et al, 2017). Furthermore, other study using the same dose of Alisk reduced levels of TNF-α and IL-6 in mice (Patel et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The Alisk in the dose of 50 mg/kg improved bone alveolar loss and decreased inflammatory process. Corroborating with the literature, the dose used in the present study was also observed to decrease blood pressure, and renin–angiotensin II level in mice and attenuated steatosis and inflammation in mice (Lee et al, 2013; Wang et al, 2015; Chen et al, 2017). Furthermore, other study using the same dose of Alisk reduced levels of TNF-α and IL-6 in mice (Patel et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…43) Another recent report indicated that ischemiareperfusion injury-induced myocardial infarction could not be decreased by aliskiren in eNOS knockout mice. 44) In contrast, pretreatment with the NOS inhibitor, L-NAME, did not reduce the infarct size induced by ischemiareperfusion injury. 45) These studies indicate that eNOS activation mediates protection against ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 93%
“…The ABTS kit instructions were followed for the ABTS assay (Beyotime, China) [ 29 ]. Briefly, ABTS solution (200 μl) and sample (10 μl) were added to each well of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%